2006
DOI: 10.1038/sj.gene.6364348
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the human cytokine response by interferon lambda-1 (IFN-λ1/IL-29)

Abstract: The interferon lambda family (IFN-l1/2/3) is a newly described group of cytokines that are related to both the type-1 interferons and IL-10 family members. These novel cytokines are induced during viral infection and, like type-1 interferons, display significant anti-viral activity. In order to understand their function in more depth, we have examined the ability of IFN-l1/IL-29 to regulate cytokine production by human immune cells. Whole peripheral blood mononuclear cells (PBMC) exposed to IFN-l1 specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 52 publications
3
97
2
3
Order By: Relevance
“…We confirmed the broad expression pattern of the IFNAR system, and found that among the cell types examined, that pDCs were the only hemopoietic cell type that responded to IFN-. Others have reported that human monocytes, blood monocyte-derived DCs, and murine intrahepatic CD3 Ϫ DX5 ϩ NK cells respond to IFN-or express the receptor chains (28,29,47,49). Therefore, we conclude that only few cell types of the hemopoietic compartment are responsive to IFN-, although we cannot exclude that expression of the type III IFN receptor system may be induced by cell differentiation and activation in a broader spectrum of cells.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We confirmed the broad expression pattern of the IFNAR system, and found that among the cell types examined, that pDCs were the only hemopoietic cell type that responded to IFN-. Others have reported that human monocytes, blood monocyte-derived DCs, and murine intrahepatic CD3 Ϫ DX5 ϩ NK cells respond to IFN-or express the receptor chains (28,29,47,49). Therefore, we conclude that only few cell types of the hemopoietic compartment are responsive to IFN-, although we cannot exclude that expression of the type III IFN receptor system may be induced by cell differentiation and activation in a broader spectrum of cells.…”
Section: Discussioncontrasting
confidence: 53%
“…Accumulating evidence now suggests that IFN-can affect the host response in a broader manner. For instance, treatment with IFN-1 induces expression of a subset of inflammatory cytokines in human monocytes and macrophages (47,48). Others have reported that human blood monocytes gain responsiveness to IFNduring differentiation to DCs, and that these DCs induce proliferation of regulatory T cells (29) and modulation of the Th1/Th2 response (49).…”
Section: Discussionmentioning
confidence: 99%
“…29 Future studies will be directed towards greater understanding of the immumomodulatory role of IFN-l1 in the human system. It will be of interest to determine which leukocyte populations are most responsive to IFN-l1 regarding CXC ELR À chemokine production (we have shown previously that monocytes are particularly responsive for cytokine secretion 26 ) and to define any cooperative effects between IFN-l1 and IFN-g.…”
Section: Induction Of Elrmentioning
confidence: 99%
“…Eight donors were examined in the present preliminary study. PBMCs were established in culture in the presence or absence of 1000 ng/ml (as described previously by Jordan et al 26 ) human IFN-l1 (Peprotech, Princeton, NJ, USA) over a time course covering 15, 30, 60, 90, 120, 180 and 240 min, and 24, 48 and 72 h. Cells were harvested, total RNA extracted (Qiagen, Valencia, CA, USA) and the levels of MIG, IP-10 and I-TAC mRNA determined by quantitative reverse transcription PCR (Q-RTPCR) relative to the housekeeping gene HPRT. The change in chemokine mRNA levels caused by exposure to IFN-l1 are shown in Figure 1.…”
mentioning
confidence: 99%
“…We have recently demonstrated that IFN-l1 will elevate IL-10 levels in in vitro cultures of human peripheral blood mononuclear cells (PBMCs) and that endogenous IL-10 can moderate IFN-l1-induced responses. 38 We wished to see whether the ability of IFNl1 to reduce IL-13 secretion was influenced by IL-10. As shown in Figure 2a, the anti-IL-10 antibody elevated the secretion of IL-13, suggesting that endogenous IL-10 in the cultures was controlling IL-13 secretion.…”
Section: Introductionmentioning
confidence: 99%